Exploring PV adoption by Non-Residential Property Owners: Applying Social Practice Theory - Reindl, Katharina; Palm, Jenny (International Journal of Sustainable Energy Planning and Management, 2024)
This article investigates the adoption of Photovoltaics (PV) systems by non-residential property owners in Sweden using a social practice theory approach. 25 semi-structured interviews were conducted with private and public non-residential property owners in the south of Sweden. The results show that about half of the property owners had had PV systems installed for a long period and had developed a PV adoption practice. These property owners had established routines within the company, aggregated relevant knowledge, and had established trusted relationships with PV installers which supported the PV adoption process. On the contrary, first-time installers and non-adopters were missing these elements and had not yet established a PV adoption practice. This study is the first step towards understanding PV adoption as a practice for non-residential property owners and contributes to an analysis of the elements that are required for a PV adoption practice to emerge. The practical relevance of the study is that it can facilitate and support non-residential property owners to adopt PV systems and contribute to a renewable electricity transition.